Accelerate Time Using the Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT) methods in the Buin Batu School Swimming Pool Pipe and Pump Machine Installation Project - Leimena, Intan Melenia; Fahmi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2024)
Time management is an important part of the implementation of construction projects. The potential for project failure will be even greater without time management. Nowadays, there are many construction projects that have poor performance in terms of time management which causes delays in work. In this final project research, one of the projects managed by PT Prima Graha Bangun Tunggal is the Buin Batu School Swimming Pool Pipe and Pump Machine Installation Project located at Batu Hijau Townsite, Sekongkang, Sumbawa Barat, Nusa Tenggara Barat, there was a delay due to a delay in the project due to structural work carried out by the main contractor has not been completed so that the sparring installation work for the pipes also experienced delays, delays in finishing work by the main contractor caused by materials arriving late at the project site, late validation or approval of material specifications from the contractor, and late material delivery due to payments that have not been made by the owner to the contractor. This study aims to accelerate time using the Critical Path Method (CPM) and Project Evaluation and Review Technique (PERT) methods in the Buin Batu School Swimming Pool Pipe and Pump Machine Installation Project. Data analysis using CPM and PERT methods is to analyze which activities are included in the critical path in order to obtain the optimal duration for the method. From the results of research using the CPM method, 11 activities were obtained in the critical path with a total duration of 114 days where this duration is 95 days faster than the duration of the plans due to the delay in the project. Meanwhile, using the PERT method, 11 activities on the critical path were obtained with a total duration of 123 days which had a difference of 86 days faster than the duration of the plans due to the delay in the project. The probability that the project can be completed in a duration of 123 days is 99.94%. From these results, it can be seen that the CPM scheduling method has the most optimal duration compared to the PERT method.